The Influence of Reward and Punishment on Employee Performance at Royal Tunjung Bali Hotel & Spa Legian - Ni Nyoman Ari Novarini; I Gusti Ayu Imbayani (International Journal of Applied Business and International Management, 2019)
This research aims to analyze the effect of Reward, and Punishment against the performance of Employees on the Royal Tunjung Bali Spa Kuta Legian & Hotel. This research method using the census to determine the number of sampelnya, with all employees so that the number of samples of research is as much as 35 employees. The data collection method using observation, interview and questionnaire presented to employees Royal Tunjung Bali Spa Kuta Legian & Hotel. Data analysis technique used is a Statistical Package for Social Science (SPSS) version 17.0. Data collection techniques used are observation, interviews, and questionnaires. Analytical techniques used was multiple linear regression analysis. The results showed that test results obtained F, with F count of 73.737 with significant value 0.000 < 0.05 then Ho is rejected, this means a variable Reward and Punishment effect simultan against variable Employee Performance. and also Reward positive and significant influence on performance of employees can be seen from the results of the test T retrieved the value T calculate the significance value 2.229 of 0.033. While the value T calculate the Punishment of 2.196 means having a significant and positive influence on performance of employees. Reward is the dominant or most variables in influencing the performance of employees. The results of this research show that the better the Reward for employees, which is supported by the existence of Punishment in the form of awarding penalties to employees who make mistakes it is able to improve the performance of employees become better again, so need to do a repair and improvement by Splurge management Tunjung Bali Hotel & Spa.